Geothermometry and Circulation Behavior of the Hot Springs in Yunlong County of Yunnan in Southwest China - Xiaocui Wang; Xun Zhou (Geofluids)
Travertine and nontravertine thermal springs have been studied in Yunlong County in southwest China to determine the geothermal reservoir temperatures and to find the geochemical processes that affect the evolution of thermal groundwater constituents during subsurface circulation. Hydrochemical characteristics distinguish travertine from nontravertine types. Travertine springs show HCO3·Cl-Na and SO4·HCO3-Ca·Na type, and a nontravertine spring presents Cl·HCO3·SO4-Na type. Log(Q/K) versus T diagrams show that reservoir temperatures can be expressed as intervals based on the equilibrium mineral assemblages coexisting in equilibrium and multiminerals in equilibrium with the aid of the PHREEQC and WATCH programs. The spring water mixing ratio with shallow water is between 59% and 82% with steam loss ranging from 12.1% to 27.8%. The Dalang Spring mixes with the highest proportion of cold water (76% to 82%) among the four hot springs and has the highest geothermal reservoir temperature (132°C to 176.9°C). The water-rock interaction during recharge from precipitation demonstrates that the minerals halite, kaolinite, chalcedony, plagioclase, and CO2(g) play an important part in the evolution of the thermal groundwater. Four inverse modeling simulation paths between precipitation and spring discharge were established to calculate the mass flux of minerals by the PHREEQC program. Halite, kaolinite, chalcedony, plagioclase, and CO2(g) participate in dissolution reactions in the thermal groundwater circulation, while gypsum, calcite, dolomite, biotite, and fluorite keep the geochemical processes in equilibrium.